The effects of forearm kinesio-taping on hand grip strength and endurance in female squash elites - Moezy, A.; Nejati, P.; Ghasemzadegan, L. (Asian Journal of Sports Medicine, 2021)
Background: Hand grip plays a fundamental role in most daily and athletic activities of the upper extremities. Objectives: The study compared the effect of various methods of forearm Kinesio-taping (KT) on the hand grip strength and endurance of Iranian elite squash players during their sporting activities at different times. Methods: Thirty-three female squash players were assigned to a quasi-experimental study, and KT was applied on their dominant forearm (on the flexor area, on the extensor area, and placebo taping). Grip strength was evaluated before, immediately, 30, and 60 minutes after KT, and grip endurance was also assessed before and 60 minutes after KT using MIE digital grip analyzer. Friedman and Kruskal-Wallis tests were used to analyze the results of grip strength, and ANOVA and the sample t-test were applied to analyze the grip endurance data. Results: The findings revealed no significant differences within the grip strength at different phases (P > 0.05). However, p values for the outcomes of KT on the flexor area?, KT on the extensor area?, and placebo mode were respectively 0.145, 0.178, 0.065 in each phase of the evaluation. A significant difference ?among KT groups and the LSD test revealed a significant increase in grip endurance in the mode of KT on the extensor area, whereas there have been no significant differences in grip endurance in KT on flexor (P = 0.785) and extensor (P = 0.457) areas. Conclusions: There was no obvious superiority of the various methods of forearm KT on grip strength at different times; nevertheless, KT was an efficient method for retaining grip endurance in squash players with no significant differences between the flexor and extensor locations.